Pelaksanaan Perkawinan Di Bawah Umur Melalui Dispensasi Pengadilan Agama Kabupaten Indramayu - Dea Agustina Suardini, Yunanto*), Mas’ut (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Nature have a nature, that if there is a man and a woman who has grown up with each other to have the appeal of each other and then the relationship continues towards a later marriage to live together. Marriage is a legal event that legal subjects do these events have to qualify. Law set the minimum age for marriage is to establish the man has reached the age of 19 years and the woman has reached the age of 16 years. But in fact there are still many imple underage marriage in Indramayu district is to ask permission to marry dipensatio Religious Court. Legal Writing aims to determine the implementation of granting dispensations to minors and consideration of the judge in giving marriage licenses under dispensation, the effectiveness of the implementation of the marriage age limit set out in the Marriage Act with the condition of the people of Indonesia, especially in the district of Indramayu.In granting the dispensation after the implementation of the requirements and application procedures are met, the court granted a dispensation for this marriage begins with the stages: First Session, session II, III trial, and then decided whether the application is rejected or granted. After the implementation of marriage is tantamount to the implementation of marriage in general. On which the judge considered that: the applicant, the reason, there is no prohibition of marriage or not, harm and benefit, as well as the ability to finance the family.Marriage Act has not been effective in reducing underage marriage because of the marriage of the Religious dispensation.